Fungal effectors versus defense-related genes of B. juncea and the status of resistant transgenics against fungal pathogens - Rai, Prajjwal; Prasad, Laxman; Rai, Pramod Kumar (Frontiers in Plant Science, 2023)
Oilseed brassica has become instrumental in securing global food and nutritional security. B. juncea, colloquially known as Indian mustard, is cultivated across tropics and subtropics including Indian subcontinent. The production of Indian mustard is severely hampered by fungal pathogens which necessitates human interventions. Chemicals are often resorted to as they are quick and effective, but due to their economic and ecological unsustainability, there is a need to explore their alternatives. The B. juncea-fungal pathosystem is quite diverse as it covers broad-host range necrotrophs (Sclerotinia sclerotiorum), narrow-host range necrotrophs (Alternaria brassicae and A. brassicicola) and biotrophic oomycetes (Albugo candida and Hyaloperonospora brassica) . Plants ward off fungal pathogens through two-step resistance mechanism; PTI which involves recognition of elicitors and ETI where the resistance gene (R gene) interacts with the fungal effectors. The hormonal signalling is also found to play a vital role in defence as the JA/ET pathway is initiated at the time of necrotroph infection and SA pathway is induced when the biotrophs attack plants. The review discuss the prevalence of fungal pathogens of Indian mustard and the studies conducted on effectoromics. It covers both pathogenicity conferring genes and host-specific toxins (HSTs) that can be used for a variety of purposes such as identifying cognate R genes, understanding pathogenicity and virulence mechanisms, and establishing the phylogeny of fungal pathogens. It further encompasses the studies on identifying resistant sources and characterisation of R genes/quantitative trait loci and defence-related genes identified in Brassicaceae and unrelated species which, upon introgression or overexpression, confer resistance. Finally, the studies conducted on developing resistant transgenics in Brassicaceae have been covered in which chitinase and glucanase genes are mostly used. The knowledge gained from this review can further be used for imparting resistance against major fungal pathogens.